Genome mining of a marine-derived Streptomyces sp. PDH23 isolated from sponge in Da Nang sea for secondary metabolite gene clusters - Ngoc Giang, Le; Thi Hong Minh, Le; Thi Quyen, Vu; Mai Anh, Nguyen; Thi Kim Cuc, Nguyen; Thi Thu Huyen, Vu (Vietnam Journal of Biotechnology, 2021)
The streptomyces is one of the best characterized ubiquitous filamentous bacteria from the actinobacteriaclass. They are known to produce thousands of specialized metabolite biosynthesis gene clusters (SMBG). Their SMBG clusters have multiple activities ranging from antimicrobial, antitumor, antiviral and probiotic. Streptomyces strain and their isolates with interesting biological activities against gram-positive and gram-negative indicator strains was recently characterised. Currently, they are employed in more than half of all antibiotics used in human and veterinary medicine. With the increase in drug resistance bacteria, it is important to mine for new natural chemicals.In this study, screening via disk-diffusion agar method revealed that Streptomyces sp. PDH23 isolated from the Rhabdastrellaglobostellata marine sponge sample from Da Nang, Vietnam produce antimicrobial agents with a wide spectrum of activities. This species can produce highly active enzymes, which breakdown celluloses, amyloses and proteins. On top of that they are shown to restrict the grow of the gram positive Bacillus cereus ATCC14579 (BC), Staphylococcus aureus ATCC25923 (SA), the gram-negativeVibrio parahaemolyticus ATCC17802 (VP) and the Candida albicans ATCC10231 fungus (CA). They are antimethicillin-resistant S. aureus(MRSA) ATCC33591 andmethicillin-resistantS. epidermidis (MRSE) ATCC35984. The taxonomy of PDH23 was characterized using 16S rRNA analysis. Whole genome sequencing of PDH23 showed 8594820 base pairs with GC content of 72.03%. Mining of secondary metabolites reveals gene clusters responsible for the biosynthesis of known and/or novel secondary metabolites, including different types of terpene, NRPS-like , PKS, PKS-like, hglE-KS, betalactone, melanin, t1pks, t2pks, t3pks, nrps, indole, siderophore, bacteriocin, ectoine, butyrolactone, phenazine.